2014
DOI: 10.3177/jnsv.60.28
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Timing of Meal Intake on Energy Metabolism during Moderate Exercise

Abstract: During exercise, the energy consumed in muscle tissue is mainly supplied by carbohydrates (CHO) and fats. In regard to health promotion and athletic sports, it is important to regulate the metabolism of these two substrates. Fats are supplied by meals, and also by adipose tissues, but CHO must be acquired from meals before exercise because little is stored as glycogen in the liver or muscle tissue. Previous studies have been conducted on the ergogenic effects of CHO feeding before exercise (1-10). It was repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
(70 reference statements)
2
6
0
1
Order By: Relevance
“…For light exercise during the early postprandial period [ 22 24 ] the overall blunting of the peak was suboptimal. Exercise during late postprandial period resulted in glycemic response similar to what was seen in the premeal studies [ 13 , 32 , 56 ]. Further, in four of the midpostprandial studies a transient rise of blood glucose was seen with increased intensity or duration of the activity signifying the arrival of endogenous glucose in the blood [ 17 19 , 44 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…For light exercise during the early postprandial period [ 22 24 ] the overall blunting of the peak was suboptimal. Exercise during late postprandial period resulted in glycemic response similar to what was seen in the premeal studies [ 13 , 32 , 56 ]. Further, in four of the midpostprandial studies a transient rise of blood glucose was seen with increased intensity or duration of the activity signifying the arrival of endogenous glucose in the blood [ 17 19 , 44 ].…”
Section: Discussionsupporting
confidence: 60%
“…The glycemic effect of light exercise during the late postprandial period (4.5 h) showed postprandial glucose elevation in people with prediabetes, reminiscent of the premeal effect [ 13 ]. Sasaki and colleagues demonstrated that the glycemic response to premeal exercise was nearly identical to that of the 4 h postmeal exercise in young trained athletes [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meal timing is another factor that may confound results, where, in the present study, ost of the included work did not control the time each meal was consumed. Meal timing can affect the circadian clock and glucose and lipids metabolism (65). Indeed, Paoli and collogues demonstrated that a regular eating pattern has potential positive effects on health outcomes, regardless of meal frequency, and the authors asserted that reduced meal frequency, following regular meal timing, may yield additional beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrates injection 30, 60 or 90 min prior to endurance running did not affect time to exhaustion (TTE), but in order to maintain normoglycaemia CHO should be consumed up to 30 min prior to running (36). In most studies, TTE or mean power in cycloergometer was not affected when CHO was consumed in different time periods prior to endurance exercise (29,32,33). Only Galloway et al (14) found significantly higher TTE when CHO was injected 30 min compared to 120 min prior to a 90% PPO cycling trial.…”
Section: Introductionmentioning
confidence: 99%